Histological and molecular investigations of the shoot apical meristem of teak (Tectona grandis linn. F.) - Haron, Mohd Rosli (2011)
Early flowering in plantation grown teak trees was reported to be controlled by both genetic and environmental factors. The first flowering occurs at the terminal of the main axis, which causes the formation of branches and forking of the main axis. The forking of the main axis at a very early stage could reduce the length of the clear bole for quality timber. Thus, the introduction of genes that turn off or delay early flowering, through molecular biology techniques and genetic engineering, can boost vegetative growth with improved tree form. This thesis reports the studies on the flowering of teak which can be divided into two major parts. The first part is on the observations made on teak flowering behavior, followed by morphological and histological observations made on several developmental stages of terminal shoots from vegetative to inflorescence. From these observations, terminal shoots from selected developmental stage were used for further molecular investigations. The second part is on the molecular investigations carried out on terminal shoots that were observed to bear floral meristem. Genes expressed in these tissues were investigated through the construction of cDNA library followed by the generation of Expressed Sequence Tags (ESTs), and Rapid Amplification of cDNA Ends-Polymerase Chain Reactions (RACE-PCR) to clone selected floral gene. Gene expression analysis using real-time PCR was carried out on selected ESTs and the cloned floral gene. Based on observations made on teak trees that grow in different plantation conditions, particularly with respect to light intensity, it was found that flowering only occurs on branches that are exposed to bright sunlight. It was also observed that flowering starts from the top branches progressing downwards to lower branches. Morphological changes of terminal shoots from vegetative to inflorescence stages were photographed and described. These morphological changes were classified into several stages named as TIS1-TIS4 (Teak Inflorescence Shoot Stages 1-4). Histological observations showed that floral meristems were only observed in TIS4 shoots. Floral meristem bearing TIS4 shoots were selected to construct two cDNA libraries with different insert size ranges;one library with 500-1500 bp and the other with 1500-5000 bp. From the cDNA library with the insert size range of 1500-5000 bp, a total of 1125 ESTs were generated. After filtering and clustering, the total of 674 nonredundants (69 consensus sequences and 605 singletons) were generated and searched for their identities through BLASTX. Five sequences were found to be related to flowering and light induction. Gene expression analysis using real-time PCR was carried out on these five selected ESTs. All the 567 nonredundants identified through BLASTX were then classified into their functional categories and their protein signatures. Simple sequence repeats (SSRs) identification was also carried on the 674 nonredundants where 21 SSRs were identified in 46 ESTs. In addition, a partial ZEITLUPE (ZTL) gene sized 1.3 kb was isolated from teak using RACE-PCR. This cloned fragment was named TgZTL (Tectona grandis ZEITLUPE) and contained a 675 bp coding region for a 225 aa residue. Gene expression analysis using real-time PCR was carried out on this partial gene.